Effectiveness of Physical Activity Interventions in Type 2 Diabetes Mellitus Patients: A Literature Review - Suardi Suardi (International Journal of Nursing and Health Services (IJNHS), 2021)
Diabetes Mellitus (DM) is a chronic disease associated with insulin deficiency and the inability of the pancreas to produce enough insulin. WHO predicts that the number of people with type II diabetes mellitus in Indonesia will increase to 12 million in 2030. The study aimed to describe Physical Activity Interventions in type 2 diabetes mellitus patients. Using the online journal database that provides free articles and journals from 2010 -2020 in PDF form such as: Scinapse, Pubmed, ProQuest, MDPI and Google Scholar using the keywords "Physical Activity", “Effectiveness of Physical Activity". Physical activity intervention can improve the condition of patient with Diabetes mellitus if routinely done. Intake of physical activity intervention can control HbA1c levels and blood sugar, body weight and other glycemic control. Physical activity intervention is able to improve the condition of Diabetes Mellitus patients